Flow hydraulic characteristics and dynamic erodibility of saline-sodic soil slopes for coastal areas under simulated rainfall conditions. Issue 5 (16th April 2022) - Liu, Dongdong; She, Dongli
ABSTRACT: Tidal flat reclamation generates several excavated saline-sodic soil slopes. However, there are limited studies on the hydraulic flow characteristics and dynamic erodibility of saline-sodic soil slopes. This study was conducted to quantify the effects of the soil bulk density (1.35 and 1.40 g cm −3 ), rainfall intensity (85, 110, and 125 mm h −1 ), and slope gradient (11°, 22°, and 35° ) on the hydraulic characteristics and soil erodibility of saline–sodic soil slopes under simulated rainfall conditions. The mean sediment loss significantly increases with the slope gradient (pr = 0.9, p < 0.01), rainfall intensity (pr = 0.6, p < 0.05), and soil bulk density (pr = 0.6, p < 0.05). The hydraulic shear stress ( τ ) and stream power ( ω ) are good sediment loss predictors for all soil bulk densities (R 2  = 0.4 and 0.6). The stream power equation SL  = Kω ( ω −  ωcr ) outperforms both hydraulic shear stress equations [ SL  = Kτ ( τ −  τcr ) 3/2 ; SL  = Kτ ( τ −  τcr )]. In most cases, the soil erodibility exponentially increases to a maximum and then exponentially decreases ( R 2  >  0.6). Consequently, the dynamic changes in the saline-sodic soil erodibility during a rainfall event cannot be neglected.